Kausalkonstruktionen mit Adjektiv im freien und fixierten Gebrauch - De Knop, Sabine; Mollica, Fabio (Linguistik Online, 2018)
The study describes the semantic and conceptual variation of causal constructions with an adjective as they are realized in German, French and Italian. In the framework of Goldberg’s (cf. 1995 and 2006) Construction Grammar, it discusses some defining properties of the analyzed constructions, like the formal and semantic (non-)predictability and their possible phraseological status based on metonymy or metaphor. Several constructions can be identified which convey different meanings, i. e. causality and/or excessiveness. The instantiations of the causal construction are linked to each other by inheritance links which make it possible to describe the variation as a network of constructions. The description of the examples’ variation with their defining properties allows us to advocate a continuum between free and fixed instantiations of the constructions and accordingly between Construction Grammar and Phraseology.